Enhancing the care of women with rheumatic diseases during pregnancy: challenges and unmet needs in the Middle East. Issue 1 (January 2016) - Al-Emadi, S.; Abutiban, F.; Zorkany, B.; Ziade, N.; Al-Herz, A.; Al-Maini, M.; Khan, B.; Ghanem, A.; Rayes, H.; Saleh, J.; Al-Osaimi, H.; Østensen, M.
Abstract Pregnancy in women with rheumatic disorders is known to be associated with risks for both the mother and fetus; however, these risks can be minimized with proper planning and careful management of the disease. In the Middle East, there are specific cultural challenges that may have a negative impact on the care that women with rheumatic disorders receive. There is a need for cross-collaboration between specialist physicians, improved awareness of rheumatic disorders among the general public and more open discussion with patients about the potential complications of pregnancy. Women in the region are often unwilling to discuss their disease with their partner and are even less likely to seek advice regarding family planning from their physician. The objective of this review is to highlight the specific challenges of pregnancy management and to discuss why establishing specialist pregnancy clinics for women with rheumatic disorders could be an effective solution. Such clinics can provide high quality care before, during and after pregnancy as shown in several European and US centers. Additionally, such clinics could be useful for the collection of pregnancy outcomes data from the Middle East, which may currently be lacking in the region, in order to highlight where further improvements can be made. With specialist care and analysis of pregnancy outcomes, the standard of care for women with rheumatic disorders in this area could be significantly improved.